Atrial Fibrillation: Development Mechanisms, Approaches and Prospects of Therapy - O. V. Sapelnikov; A. A. Kulikov; D. I. Cherkashin; I. R. Grishin; O. A. Nikolaeva; R. S. Akchurin (Рациональная фармакотерапия в кардиологии)
Atrial fibrillation (AF) is the most common arrhythmia. It is diagnosed in more than 33 million people worldwide and is the leading cause of hospitalization for arrhythmias. AF is characterized by fast and irregular atrial activation without discrete P-waves at a surface electrocardiography. AF pathophysiological mechanisms are very complex and include the dynamic interaction between arrhythmia substrate and triggers. Consequently, the clinical search for effective therapeutic targets should include the entire process of the onset and progression of the disease: from the first paroxysms to the development of a stable permanent form of AF.